Development of alkylamine-functionalized graphene oxides and its composites with metal disulfides as friction modifier and anti-wear additives in lubricating oil / Nurul Athirah Ismail - Nurul Athirah, Ismail (2022)
More than half of a vehicle’s fuel consumption is spent overcoming friction in moving mechanical systems. Friction-related losses directly impact fuel consumption and fuel economy. Thus, increased sales of motorcycles, cars, and other vehicles increased the demands and consumption of automotive lubricant and lubricant additives to minimize friction and enhance fuel economy. Graphene was selected as the starting material to be synthesized as a friction modifier and anti-wear additives. Its excellent performance in minimizing friction and wear, excellent mechanical strength, chemical inertness, are easily sheared, and provides the lamellar mechanism of lubrication. However, graphene does not disperse in oil and is prone to settling at the bottom, forming sediments, limiting its use as lubricant additives. Exploration of graphene-based material in lubricants is a novel endeavor, and the literature on it remains limited. Graphene was functionalized to improve its dispersion stability in oil via attachment of a polar head and long straight hydrocarbon tail to make it more suitable for use as lubricant additives. The covalent functionalization method via amidation reaction was selected to attach the polar head and straight hydrocarbon tails by grafting alkylamine to the graphene, taking advantage of the multiple oxygen-containing functional groups on graphene oxide (GO). Besides improving its dispersion stability in oil, the tribological performance was further enhanced by the attachment of metal disulfide on the surface of the functionalized graphene. Composites of functionalized graphene were prepared at multiple mass ratios of functionalized graphene and metal disulfide, and the composites showed significant improvement in tribological performance, confirming their suitability as lubricant additives.